"UNABLE TO RESIST": ON THE "POSSIBILITY" OF "IMPOSSIBILITY" AND CHRISTOPHE BOUTON'S TIME AND FREEDOM. Issue 3 (5th September 2017) - Wilkerson, Dale A.
ABSTRACT: This essay reflects critically on Martin Heidegger's remarks about authenticity and death with the aid of Christophe Bouton's Temps et libert é (2002), translated by Christopher Macann as Time and Freedom (2014). It first raises general questions concerning the possible thematic relationship between human endeavoring (action) and the experiences of finitude and freedom. Heidegger's Being and Time is particularly useful for exploring this relationship, but certain problems emerge when using this text for accessing the essay's themes. To wit: there are good reasons for mistrusting readings of Being and Time as a "practical" guide for grounding action. Against the practical reading, the essay wishes to reclaim the ontological‐existential significance of Heidegger's text. Although Bouton's treatment of Being and Time excludes its ontological dimensions and is entirely practical, even to the point of disregarding certain theoretical risks inherent in this approach, Bouton's study is indispensable for situating Being and Time in a historical‐intellectual context, whereby the experiences of freedom and time are understood within certain metaphysical presuppositions rendering them difficult to establish together on reliable grounds. Following Bouton's lead, the essay shows that the hermeneutic differences between practical and ontological readings of Being and Time can be explored through reflections on what Heidegger might have meant by the term " Möglichkeit" ("possibility"), from which Bouton infers "freedom." It is alleged that Bouton does not fully consider all of Heidegger's assertions regarding Möglichkeit, most problematically the claim that the human being's most essential "possibility" is its "impossibility, " that is to say, its death.